1996
DOI: 10.1007/bf03079319
|View full text |Cite
|
Sign up to set email alerts
|

De effecten van psychologische behandeling van depressies. Een overzicht van meta–analyses

Abstract: De effecten van psychotherapie bij unipolaire depressies zijn in tal van studies onderzocht. Tot op heden zijn negen meta-analyses van de effecten van psychotherapie bij depressies uitgevoerd. Uit deze analyses blijkt dat de effecten van deze behandelvormen redelijk groot zijn. Wel blijven patie¨nten na behandeling gemiddeld iets depressiever dan de algemene bevolking. Psychotherapie is ongeveer even effectief als farmacologische behandeling. Er is geen verschil in effectiviteit tussen de verschillende soorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
6

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
1
28
1
6
Order By: Relevance
“…Accordingly, psychological treatments do have significant effects in PPD, but the effect size that we found indicated somewhat smaller effects than are usually found for psychological treatments (Churchill et al, 2001;Cuijpers & Dekker, 2005). Biological treatments such as pharmacological treatment and electroconvulsive therapy also find higher effect sizes.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Accordingly, psychological treatments do have significant effects in PPD, but the effect size that we found indicated somewhat smaller effects than are usually found for psychological treatments (Churchill et al, 2001;Cuijpers & Dekker, 2005). Biological treatments such as pharmacological treatment and electroconvulsive therapy also find higher effect sizes.…”
Section: Discussioncontrasting
confidence: 53%
“…We identified these abstracts by combining terms indicative of psychological treatment (i.e., psychotherapy, psychological treatment, cognitive therapy, behavior therapy, interpersonal therapy, reminiscence, life review) and depression (both MeSH-terms and textwords). For this database, we also collected the primary studies from 22 metaanalyses of psychological treatment of depression (Cuijpers & Dekker, 2005). We retrieved a total of 766 articles for further study.…”
Section: Search Strategy and Selection Of Studiesmentioning
confidence: 99%
“…These abstracts were identified by combining terms indicative of psychological treatment and depression (both MeSH terms and text words). In addition, the primary studies from 22 meta-analyses of psychological treatment of depression 26 were collected and the references of included studies were examined. A total of 857 published papers and 33 dissertations were retrieved for further study ( Figure 1).…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Unpublished studies were searched through a search of Dissertation Abstracts. Second, we examined the references of the six meta-analyses described above and four systematic reviews (Schneider and Olin, 1995;Cole et al, 2000;Arean and Cook, 2002;Blazer, 2003), which were identified in a systematic review of meta-analyses of psychological treatments for depression (Cuijpers and Dekker, 2005). And third, we examined the references of retrieved papers.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…In a systematic review of meta-analyses of psychological treatments for depression in all age groups (Cuijpers and Dekker, 2005), we identified six meta-analyses of psychological treatments for depression in late life (Scogin and McElreath, 1994;Koder et al, 1996;Engels and Vermey, 1997;Cuijpers, 1998;McCusker et al, 1998;Gerson et al, 1999). None of these meta-analyses, however, has focused on randomized controlled trials only, and all also included studies in which the respondents were not allocated randomly to conditions, while this is known to be the most crucial element of being sure that a treatment effect can actually be attributed to the treatment (Higgins and Green, 2005).…”
Section: Introductionmentioning
confidence: 99%